The art of interpretation: around a rondo - behind the performance - Emmerson, Stephen; Mohrholz, Kai (Queensland Griffith University, 2006)
This DVD/DVD-ROM set represents a unique insight into the realities of being a contemporary performer of Western classical music.Emmerson traces in great detail his journey to interpret Mozart's Rondo in A Minor K511 on piano and fortepiano, referring to scores, technical challenges, period and contemporary literature on musical interpretation, recordings by other artists, and the arduous process that takes place in the musician's studio.This publication is an invaluable resource to advanced music students and all those fascinated by the art of interpretation.Featuring Stephen Emerson with Angela Turner